Mortality events resulting from Australia's catastrophic fires threaten aquatic biota - Silva, Luiz G. M.; Doyle, Katherine E.; Duffy, Deanna; Humphries, Paul; Horta, Ana; Baumgartner, Lee J. (Global change biology, 2020)
The consequences of the 2019–2020 bushfires in Australia were also devastating for the aquatic biota. Following abnormal rainfall events in burnt areas, widespread mortality events including fish and invertebrates were recorded in estuarine and freshwater systems. Such negative impacts on aquatic resources highlight the need to include these ecosystems in bushfire recovery plans. Management should prioritise catchments at higher risks of further negative impacts and research must be conducted to understand the efficacy of actions post‐fire.